2018
DOI: 10.3892/etm.2018.6106
|View full text |Cite
|
Sign up to set email alerts
|

Acquired hypophosphatemic osteomalacia is easily misdiagnosed or neglected by rheumatologists: A report of 9 cases

Abstract: The aim of the present study was to assist rheumatologists in differentiating hypophosphatemic osteomalacia (HO) from mimic rheumatology diseases. Clinical data was obtained from 9 patients with acquired HO, initially misdiagnosed as mimic rheumatologic diseases. The data were retrospectively analyzed and a literature review was performed. The etiology of the cases was as follows: Adefovir dipivoxil-induced Fanconi syndrome was present in 6 of the cases, 2 were tumors and 1 case was chronic nephropathy. The ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…Endocal Forte OD, Protocol Supplement 2tsp with milk BD Adophos Sachet in ½ glass of Water QID, Tab. Rocaltrol (2.5) QID, average Patient were walking without support in an average 2 weeks, Pain decreased and also there is improvement of haematological parameter , X-ray shows signs of healing fracture These findings are similar to LING LI [14] et al they found Clinical data was obtained from 9 patients with acquired HO, initially misdiagnosed as mimic rheumatologic diseases. The data were retrospectively analyzed and a literature review was performed.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Endocal Forte OD, Protocol Supplement 2tsp with milk BD Adophos Sachet in ½ glass of Water QID, Tab. Rocaltrol (2.5) QID, average Patient were walking without support in an average 2 weeks, Pain decreased and also there is improvement of haematological parameter , X-ray shows signs of healing fracture These findings are similar to LING LI [14] et al they found Clinical data was obtained from 9 patients with acquired HO, initially misdiagnosed as mimic rheumatologic diseases. The data were retrospectively analyzed and a literature review was performed.…”
Section: Discussionsupporting
confidence: 76%
“…Typically, HO is either inherited [9] , a result of tumor-induced osteomalacia (TIO) [11] , druginduced [10] or a symptom of chronic kidney disease [12] . Patients with inherited or TIO have been widely reported on by endocrinology or oncology specialists, however HO is often misdiagnosed in clinical practice as ankylosing spondylitis (AS), chronic arthritis, lumbar disc disease, osteoporosis and somatoform disorder, as it typically presents with the same signs and symptoms of these rheumatologic diseases, including bone pains, thoracic or back pain, muscle weakness, proximal myopathy and arthralgia [14] . Diagnosis of HO remains a challenge to rheumatologists and physicians due to its low prevalence and nonspecific manifestations.…”
Section: Discussionmentioning
confidence: 99%
“…The main characteristics of 32 patients with ADV-induced FS, including eight patients in our institution and 24 published cases, are summarized in Table 4 . 5 , 18 , 22 , 23 , 36 43 …”
Section: Reviewmentioning
confidence: 99%
“…Moreover, a study using a 6‐month follow‐up period found that patients with chronic kidney disease and tubule acidosis have a poor prognosis. 22 …”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation